MAGNETIC RESONANCE IMAGING FINDINGS ASSOCIATED WITH ULNAR COLLATERAL LIGAMENT TEARS IN ADOLESCENT BASEBALL PITCHERS. Issue 3 (31st March 2019) - Cox, Ben; Plummer, Hillary; Goodrich, Eric; Andrews, James; Saper, Michael
BACKGROUND: The number of ulnar collateral ligament (UCL) injuries in adolescent baseball pitchers has risen over the past 2 decades with the incidence of UCL reconstructions also increasing dramatically over that time period. The Joyner-Andrews magnetic resonance imaging (MRI) classification of UCL tears has previously been described to describe the grade and location of tears, which can aid in surgical decision-making. However, the classification of UCL tears in the at-risk adolescent population has yet to fully investigated. Improving our knowledge of these injuries is crucial to help drive targeted evidence-based treatment strategies. The purpose of this study was to examine the grade and location UCL tears using the Joyner-Andrews MRI classification in a large group of adolescent baseball pitchers. METHODS: We reviewed 225 symptomatic adolescent (aged =19 years) male baseball pitchers with UCL injuries treated by the senior author from 2007-2016. All patients had failed conservative treatment prior to evaluation. Pitchers with a prior history of elbow surgery were excluded. Plain radiographs and MRI arthrograms were evaluated for each patient to categorize the UCL injury and associated pathology. The images were reviewed by a sports medicine-trained orthopedic surgeon. UCL tear grade and location were classified using the Joyner-Andrews classification. RESULTS: The mean age at the time of evaluation was 17.2 ± 1.5 years. 56% of the patients were high school athletes. The majority (59.1%) of UCL tears were high-grade partial tears (Type II). Of those 53.4% were on the humeral side (Type II H). The least common tear types were low-grade partial tears (I) and tears in more than one location (Type IV) in 1.3% and 0.9% of patients, respectively. Plain radiographs revealed 31.4% of patients had abnormal findings; calcifications and olecranon osteophytes were present in 10% and 13% of patients, respectively and more commonly occurred in patients with Type II tears. CONCLUSIONS: The results of this study showed that the majority of adolescent baseball pitchers (59%) sustain high-grade partial tears of the UCL. These findings suggest that effective non-reconstruction options such as platelet-rich plasma and UCL repair with internal brace augmentation could be ideal alternatives to UCL reconstruction for these young patients. The high percentage of radiographic abnormalities in these patients highlights the adaptive changes about the elbow in response to the repetitive stresses experienced by the young elbow during throwing.